SOCIALIZATION OF CLOTHES FRAGRANCE MANUFACTURING AS A BUSINESS OPPORTUNITY FOR THE COMMUNITY - Maria Ulfa; Elfrida Elfrida; Nurlaila Hanum (LPPM dan PM Universitas Samudra, 2022)
Community Service is one of the Tridharma of Samudra University. The implementation of this service is in the form of outreach and training in making clothes perfume as a business opportunity for the people of Paya Bedi Village, Rantau District, Aceh Tamiang Regency in the form of training which is easy to learn and the price is easy to reach. These skills are very useful and will generate business opportunities for the community which can be sold at very profitable prices. The aim of this training is to teach housewives knowledge as additional income for the family. The method of community service training activities is the lecture and experimental method. The results obtained are an increase in the creativity of knowledge in housewives about making clothes perfume.